The generalized Chen-Lee-Liu model with higher order nonlinearity: optical solitons - Gomez, Cesar A.; Rezazadeh, Hadi; İnç, Mustafa; Akinyemi, Lanre; Nazari, Fakhroddin (Springer, 2022)
A special type of equation which have variable coefficients and contains terms with higher order nonlinearity is studied. We give conditions under which exact solutions for it can be obtained using a special computational method. From the solutions presented here, novel traveling wave solutions for the Chen-Lee-Liu (CLLE) are presented. Finally, we give some conclusions.
Keywords: CLLE; Variable coefficients; Exact solutions; Computational method